Use of botulinum toxin in urology: a literature review - (:unkn) unknown (AVES PRESS LTD, 2017)
Botulinum neurotoxin (BoNT) is currently preferred as a minimally invasive treatment for lower urinary tract pathologies. Although BoNT injections have become widespread globally for the past 5 years, today, the urological use of BoNT Type A (BoNT-A) is only licensed for the treatment of neurogenic detrusor overactivity and overactive bladder. Despite the relative evidence for the use of BoNT-A in benign prostatic enlargement, there is no high-level evidence data for the use in detrusor sphincter dyssynergia, interstitial cystitis/bladder pain syndrome, and chronic pelvic pain. In this comprehensive review, we mention the mechanism of action and efficacy of BoNT in various urological disorders, present the reliability, and evaluate the literature data supporting its use.
Keywords: Botulinum toxin; neurogenic detrusor overactivity; overactive bladder; detrusor sphincter dyssynergia; benign prostatic enlargement; interstitial cystitis; DETRUSOR-SPHINCTER DYSSYNERGIA; BENIGN PROSTATIC HYPERPLASIA; PLACEBO-CONTROLLED TRIAL; URINARY-TRACT DISORDERS; CORD-INJURY PATIENTS; OVERACTIVE BLADDER; A TOXIN; DOUBLE-BLIND; CERVICAL DYSTONIA; INCONTINENCE